Spectral tunability and enhancement of molecular radiative emission by metal-dielectric-metal stratified plasmonic nanostructure - Golmakaniyoon, Sepideh (2017)
Plasmonic nanostructures have been widely known for their notable capability to enhance spontaneous emission of an electric dipole in their vicinity. Due to the availability of large optical density of states at their metallic surface, the radiative and nonradiative decay channels are dramatically modified. However, enhancement cannot be realized for any desired emissive dipole as the plasmonic resonance frequency is mostly determined intrinsically by the existing plasmonic materials. Although recent studies using metamaterial structures demonstrate a promising approach of tuning the Purcell factor across the emission wavelength, many of the demonstrations lack efficient radiative emission besides the fabrication complexity. Here, we show theoretically and experimentally that a simple metal-dielectric-metal stratified architecture allows for high tunability of the resonance frequency to obtain a maximum radiative decay rate for any desired dipole peak emission wavelength. Owing to the effective cascaded plasmonic mode coupling across the metal-dielectric interfaces, the proposed approach uniquely provides us with the ability to optimize the plasmonic nanostructure for 100% radiative transmission and 3-fold radiative emission enhancement.